Problems in paradise? : Changes and challenges to Swedish democracy - Silander, Daniel (Emerald Publishing Limited, 2024)
Just 25 years ago, Europe was engaged in a process of democratization and integration. The EU, with an expanded number of member-states, became a symbol of a democratic, peaceful and prosperous Union. However, recent years have seen the reversal of democratization in many of the countries that went through political transition in the 1990s. Even in established democracies, growing authoritarian tendencies have been apparent in the rise of populism and political polarisation and questions over the rule of law. Focusing on threats to Swedish liberal democracy in a time of autocratization to explore wider crises democracy is currently facing around the globe, Problems in Paradise? explores eight interactive sub-societies crucial for a dynamic and persistent liberal democracy: the political, the judicial, the bureaucratic, the economic, the educational, the media, the civil, and the international. Fully embracing the wide range of challenges liberal democracy has faced in recent years, this book offers a deepened understanding of contemporary changes and challenges to liberal democracy.
Includes index.
Keywords: Democracy -- Sweden.; Sweden -- Politics and government -- 21st century.; Political Science -- Political Ideologies / Democracy.; Political structures: democracy.; elektronické knihy; electronic books